2013
DOI: 10.1021/am4006989
|View full text |Cite
|
Sign up to set email alerts
|

Superior Performance of Copper Based MOF and Aminated Graphite Oxide Composites as CO2 Adsorbents at Room Temperature

Abstract: New composites Cu-BTC MOF and graphite oxide modified with urea (GO-U) are developed and tested as CO2 adsorbents at room temperature. The composite containing GO-U with the highest nitrogen content exhibits an excellent CO2 uptake (4.23 mmol/g) at dynamic conditions. The incorporation of GO-U into MOF changes the chemistry and microstructure of the parent MOF and results in synergistic features beneficial for CO2 retention on the surface. To identify these features the initial and exhausted materials were ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 65 publications
7
72
0
Order By: Relevance
“…Therefore, MOFs are widely regarded as versatile materials for separation, storage, drug delivery, catalysis, etc. [7][8][9][10]. Thousands of MOF structures have been synthesized and their numbers are still growing [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MOFs are widely regarded as versatile materials for separation, storage, drug delivery, catalysis, etc. [7][8][9][10]. Thousands of MOF structures have been synthesized and their numbers are still growing [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Recently, there is an increasing trend in using luminescence MOFs to probe guest species, and thus developing multifunctional MOFs combining luminescence and other promising applications, such as magnetism and biomedicine. [7][8][9][10][11] However, only very limited MOFs for simultaneously detecting diverse kinds of analytes were investigated; [12][13] quite few luminescent MOF sensors have been discovered capable of quantitative detection up to now.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it was found that graphene oxide (GO), multi‐walled carbon nanotube (MWCNT), AC doping MOFs can both enhance porosity of the composite materials to improve its adsorption properties of gas . As far as the early report, GO could increase the MOF adsorption capacity substantially . However the adsorption of MOF@GO may be not stable, because that GO has serious deficiency of the coordination of particles so as to make them easy to accumulate .…”
Section: Introductionmentioning
confidence: 96%